Glycan specificity of neuraminidases determined in microarray format. (16th June 2016) - McCombs, Janet E.; Diaz, Jason P.; Luebke, Kevin J.; Kohler, Jennifer J.
Highlights: Desialylation of glycans by neuraminidases can be detected by chemoselective labeling. Chemoenzymatic labeling of unsialylated glycans can be performed on glass slides. Three pneumococcal neuraminidases exhibit distinct glycan specificities. Graphical abstract: Abstract: Neuraminidases hydrolytically remove sialic acids from glycoconjugates. Neuraminidases are produced by both humans and their pathogens, and function in normal physiology and in pathological events. Identification of neuraminidase substrates is needed to reveal their mechanism of action, but high-throughput methods to determine glycan specificity of neuraminidases are limited. Here we use two glycan labeling reactions to monitor neuraminidase activity toward glycan substrates. While both periodate oxidation and aniline-catalyzed oxime ligation (PAL) and galactose oxidase and aniline-catalyzed oxime ligation (GAL) can be used to monitor neuraminidase activity toward glycans in microtiter plates, only GAL accurately measured neuraminidase activity toward glycans displayed on a commercial glass slide microarray. Using GAL, we confirm known linkage specificities of three pneumococcal neuraminidases and obtain new information about underlying glycan specificity.